(3dWGFa Gdeff aj efGbH GdTjN CHj GdYHGS GdeQSi hTjNg CHj GdMSf GdTGPdis - (3CMeO Hf eMeO Hf YHO GdcQje Hf YWGA Gddg GdScfOQj, GHf YWGA Gddg , JGL GdOjf CHh GdaVd,J (B709 (3g` s
(3ChdgG (B:s
(3CeG HYO , aEfj bUOJ aj gPG GdcJGH Cf CPcQ LedkG ef aVGFd TgGH GdOjf CHj GdYHGS GdeQSj s
(3BNQgG (B:s
(3dGLYd Gddg eG fbhdg heG fSeYg MLI YdjfG hGdMeO ddg QH GdYGdejf s
(3HBNQgG bUjOI HGFjI hCOYjIs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B221 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B121s
Keywords: (3GdJGQjNs